New DMSP database of precipitating auroral electrons and ions. Issue 8 (10th August 2017) - Redmon, Robert J.; Denig, William F.; Kilcommons, Liam M.; Knipp, Delores J.
Abstract: Since the mid‐1970s, the Defense Meteorological Satellite Program (DMSP) spacecraft have operated instruments for monitoring the space environment from low Earth orbit. As the program evolved, so have the measurement capabilities such that modern DMSP spacecraft include a comprehensive suite of instruments providing estimates of precipitating electron and ion fluxes, cold/bulk plasma composition and moments, the geomagnetic field, and optical emissions in the far and extreme ultraviolet. We describe the creation of a new public database of precipitating electrons and ions from the Special Sensor J (SSJ) instrument, complete with original counts, calibrated differential fluxes adjusted for penetrating radiation, estimates of the total kinetic energy flux and characteristic energy, uncertainty estimates, and accurate ephemerides. These are provided in a common and self‐describing format that covers 30+ years of DMSP spacecraft from F06 (launched in 1982) to F18 (launched in 2009). This new database is accessible at the National Centers for Environmental Information and the Coordinated Data Analysis Web. We describe how the new database is being applied to high‐latitude studies of the colocation of kinetic and electromagnetic energy inputs, ionospheric conductivity variability, field‐aligned currents, and auroral boundary identification. We anticipate that this new database will support a broad range of space science endeavors from single observatory studies to coordinated system science investigations. Plain Language Summary: Since the mid‐1970s, the Defense Meteorological Satellite Program (DMSP) spacecraft have operated instruments for monitoring the space environment from low earth orbit. We describe the creation of a new public database of auroral charged particles provided in a common and self‐describing format that covers 30+ years of DMSP spacecraft from F06 (launched in 1982) to F18 (launched in 2009). This new database is accessible at the National Centers for Environmental Information (NCEI) and the Coordinated Data Analysis Web (CDAWeb). We anticipate that this new database will support a broad range of space science endeavors from single observatory studies to coordinated system science investigations. Key Points: DMSP SSJ precipitating electron and ion observations upgraded Fluxes are derived from newly decontaminated count rates and calibration factors Uncertainties are estimated, and ephemeris is improved